Differential survival of nursery‐reared Acropora cervicornis outplants along the Florida reef tract. Issue 1 (4th November 2020) - van Woesik, Robert; Banister, Raymond B.; Bartels, Erich; Gilliam, David S.; Goergen, Elizabeth A.; Lustic, Caitlin; Maxwell, Kerry; Moura, Amelia; Muller, Erinn M.; Schopmeyer, Stephanie; Winters, R. S.; Lirman, Diego
Abstract : In recent decades, the Florida reef tract has lost over 95% of its coral cover. Although isolated coral assemblages persist, coral restoration programs are attempting to recover local coral populations. Listed as threatened under the Endangered Species Act, Acropora cervicornis is the most widely targeted coral species for restoration in Florida. Yet strategies are still maturing to enhance the survival of nursery‐reared outplants of A. cervicornis colonies on natural reefs. This study examined the survival of 22, 634 A. cervicornis colonies raised in nurseries along the Florida reef tract and outplanted to six reef habitats in seven geographical subregions between 2012 and 2018. A Cox proportional hazards regression was used within a Bayesian framework to examine the effects of seven variables: (1) coral‐colony size at outplanting, (2) coral‐colony attachment method, (3) genotypic diversity of outplanted A. cervicornis clusters, (4) reef habitat, (5) geographical subregion, (6) latitude, and (7) the year of monitoring. The best models included coral‐colony size at outplanting, reef habitat, geographical subregion, and the year of monitoring. Survival was highest when colonies were larger than 15 cm (total linear extension), when outplanted to back‐reef and fore‐reef habitats, and when outplanted in Biscayne Bay and Broward–Miami subregions, in the higher latitudes of the Florida reef tract. This study points to several variables that influence the survival of outplanted A. cervicornis colonies and highlights a need to refine restoration strategies to help restore their population along the Florida reef tract.